Characteristics of Chlorella sp Biomass Immobilized on Chitosan (Chlo-Kit) for Adsorption of Chromium(III) Solution - Titin Anita Zaharah; Anis Shofiyani; Endah Sayekti (ALCHEMY Jurnal Penelitian Kimia, 2016)
Properties of biosorbent prepared from biomass of Chlorella sp immobilized on chitosan (Chlo-Kit) have been studied for adsorption of Chromium(III). Chlo-Kit adsorbent prepared by following steps: dissolving chitosan to get hydrogel form, immobilization of biomasson chitosan hydrogel, beads formation and crosslinkingthe adsorbent beads using epichlorohydrin reagent.Characterization using FT-IR spectrophotometry  and SEM showed that mechanism of biomass immobilization on chitosan involves electrostatic interactions between the functional groups of such both materials. Biomass immobilized on chitosan (Chlo-Kit) showed the higher stability in acid medium than un-immobilized biomass. Adsorption of Cr(III) metal ion on Chlo-Kit occured at optimum pH of 4-5 and followed well the Langmuir adsorption isotherm model. The adsorption capacity of Cr(III) on Chlo-Kit was 68.965 mg/g, about 91% higher than that on Chlorella biomass